Effect Of Covid-19 On The Mental Health Status Of Males In Himachal Pradesh: A Comparative Study - Bala, Jyoti; Sharma, Sanjay; Sharma, Rubina (Journal of Neonatal Surgery, 2025)
The present study explores the impact of COVID-19 on the mental health status of males residing in Himachal Pradesh. A quantitative research design was employed to meet the objectives of the study. Data were collected from 300 male participants across five districts of Himachal Pradesh: Lahaul & Spiti, Kullu, Mandi, Una, and Shimla. To ensure a comprehensive assessment of individuals affected by COVID-19, the participants were categorized into three groups: infected but non-hospitalised, infected and hospitalised, and non-infected individuals. The collected data were then subjected to statistical analysis to identify variations in mental status among these groups. The findings revealed a statistically highly significant difference in mental health status across all three categories/groups